Stimulation with a class A CpG oligonucleotide enhances resistance to infection with feline viruses from five different families - Robert-Tissot, Céline; Rüegger, Vera L; Cattori, Valentino; Meli, Marina L; Riond, Barbara; Moore, Peter F; Engels, Monika; Franchini, Marco; Hofmann-Lehmann, Regina; Lutz, Hans (Veterinary research (Paris), 2012)
Domestic cats are commonly affected by viral pathogens that induce lengthy infections with fatal outcomes. Prevention of viral propagation is of primordial importance in shelters and catteries, where cats from different backgrounds have narrow contacts. Oligonucleotides (ODN) containing cytosine-phosphate-guanosine motifs of class A (CpG-A) are highly potent synthetic inducers of innate antiviral mechanisms. The aim of this study was to test their ability to modulate innate immune responses and prevent viral replication as stand-alone agents in the domestic cat. CpG-A stimulation of feline peripheral blood mononuclear cells (PBMCs) enhanced their proliferation, increased the presence of co-stimulatory molecules on their surface and influenced their gene expression profiles in an antiviral orientation. Incubation of the supernatants of CpG-A stimulated PBMCs with feline cell lines of epithelial and fibroblastic origin induced expression of the antiviral myxovirus resistance (Mx) gene in these target cells, which also showed enhanced resistance to feline viruses from five distinct families, namely Coronaviridae , Herpesviridae , Caliciviridae , Parvoviridae , and Retroviridae . Most importantly, subcutaneous administration of CpG-A in domestic cats systemically increased the expression of Mx, reaching maximal levels within 24 h. Plasma from treated cats could furthermore inhibit viral replication in vitro . Altogether, our data highlight the promising potential of CpG-A to induce a preventive antiviral state in the cat and to protect feline populations against a broad range of virus infections.